The concept of synthesis of one class of self-synchronizing discrete signals - Gorbenko, I.D.; Potii, O.V.; Zamula, A.A. (Radiotekhnika, 2021)
The use of broadband signals (BSS) makes it possible to increase the noise immunity of information and communication systems (ICS) when exposed to structural (mutual) and organized interference. The real noise immunity will be lower than the potential one. The reason for the decrease in noise immunity, when entering synchronism and when distinguishing signals, is the presence of side peaks of the correlation functions. Proceeding from this, the NLS used in ICS should have such correlation properties when the side peaks of the NLS CF are as small as possible, i.e. ideally should tend to zero. In this case, it is necessary to determine the influence of side peaks on the characteristics of signal detection, measure their parameters, distinguish signals, and find the conditions for obtaining small side peaks. The problem of synthesizing a class of signals with given correlation, ensemble and structural properties, as well as properties of "blurring" in correlation characteristics, is formulated and solved in general form. The specified property ("fuzziness") means that increasing or decreasing the length of the discrete signal does not change the correlation properties of the discrete sequence on the basis of which the signal is synthesized. The use of many of these signal systems in modern information and communication systems will improve the performance indicators of such systems, first of all, noise immunity, secrecy, information security, noise immunity of signal reception.